Linking Higher Education and Economic Development Implications for Africa from three successful systems - Pillay, Pundy (African Minds, 2012)
Finland, South Korea and the state of North Carolina in the United States are three systems that successfully have harnessed higher education in their economic development initiatives. Common to the success of the all these systems is, amongst others, the link between economic and education planning, quality public schooling, high tertiary participation rates with institutional differentiation, labour market demand, cooperation and networks, and consensus about the importance of higher education for development. Linking higher education and economic development: Implications for Africa from three successful systems draws together evidence on the three systems, synthesises the key findings, and distils the implications for African countries.